Selected cartographic sources from the late 18th century to 1939 for the research of Josephine colonization in the Austrian sector of the first partition of Poland - Cepil Monika (Polish Cartographical Review)
The article presents a selected base of cartographic sources enabling analyses on Josephine settlements in the Austrian partition from the late 18th century to 1939. The purpose of the article is to present the cartographic source base on Josephine colonization collected in Poland and Ukraine. The research covered all settlements created during the Josephine colonization (1781–1789). The text discusses cartographic source materials (available on-site and online) acquired through queries. The analyses included village plans, large--scale maps of Galicia, the Galician cadastre (Austrian land cadastre) and maps from the interwar period.